Influence of anxiety and body dissatisfaction on risky eating behaviors in a Mexican sample of female adolescents (European Journal of Child Development, Education and Psychopathology, 2021)
Body dissatisfaction (BD) is an important predictor of risky eating behaviors (REB), although BD commonly presents with symptoms of anxiety, it is unknown if this moderates the relationship between BD and REB in the adolescent population. Objective: to analyze the moderating effect of anxiety symptoms in the relationship between BD and REB. Method: Explanatory cross-sectional study. Non-probabilistic sampling n = 500 female adolescents in school, ages between 14 and 19 years old (M = 16.81, SD = 1.33). The participants answered the Eating Attitudes Test-26, Body Shape Questionnaire-8D and Hospital Anxiety and Depression Scale. Informed consent was obtained from parents and informed consent from participants. Results: anxiety symptoms moderated the relationship between BD and REB, a stronger association in high levels of anxiety (b = .51, p
Keywords: Anxiety; Adolescents; Risky Eating Behaviors; Body dissatisfaction